Protótipo de prótese testicular paciente-específico produzido com ácido polilático e revestido com cianocrilato ou polimetilmetacrilato - Ferreira, Camila Calvi Menegassi (2023)
In order to reduce the psychological and aesthetic consequences caused by elective or therapeutic orchiectomy, we developed two types of testicular prostheses, which were produced using a 3D printer, with polylactic acid filament, and coated with cyanoacrylate or polymethylmethacrylate (PMMA). They were tested in Wistar rats, with orchiectomy performed on the left testicle and the prosthesis implanted inside the tunica vaginalis, in group 1 we implanted the prosthesis coated with cyanoacrylate and in group 2 with PMMA. The implants showed interesting features such as low cost, reduced production time, and ease of customization for the patient. Two rats in group 1 had monocular vaginalitis in the region of the tunica vaginalis implant and 3 (3/10, 30%) had fibrous dermatitis. In group 2, 5 rats (50%) had fibrous dermatitis, and none had alterations in the tunica vaginalis. We performed a logistic regression model, the results showed no significant association between the type of prosthesis and the presence of inflammation in the tunica vaginalis (p=0.08) or fibrous dermatitis (p=0.22). However, we suggest further studies with cyanoacrylate. PMMA proved to be an excellent option as a biomaterial for prosthesis. Fibrous dermatitis occurred due to the dermal healing process caused by the surgical incision.